MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL COOPERATIVE LEARNING TIPE CIRC DALAM PEMBELAJARAN GEOGRAFI MATERI BENCANA ALAM KELAS X SMA NEGERI 2 HALMAHERA SELATAN - Jaka, Rosmiyanti; Suaema, Andi; Hi. Halek, Dahri (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
The purpose of this study was to determine the improvement of student learning outcomes through the CIRC Type Cooperative Learning Model in geography learning for class X of SMA Negeri 2 Halmahera Selatan. This type of research is classroom action research (CAR) using quantitative research methods. The subjects of this study were students of class X of SMA Negeri 2 Halmahera Selatan with a total of 41 students. Improvement of student learning through the CIRC Type Cooperative Learning Model in geography learning for class X of SMA Negeri 2 Halmahera Selatan. There is an increase in student learning outcomes by applying the CIRC method. This can be proven by the achievement of student learning outcomes in cycle I with an average learning outcome of 59.51 while cycle II with an average learning outcome of 80.14 and has reached the specified classical KKM of 70.